(untitled) (International Journal of Food and Nutritional Sciences, 2024)
Abstract An online vegetable sales application allows customers to easily purchase fresh, locally sourcedvegetablefrom theirphoneorcomputer.Withauser-friendlyinterface,customers can browse and select from a wide variety of fruits and vegetables, customize their order, and choose a delivery or pickup option that works for them. The purpose of this project is toreacheverycornerofthecountrywhereinternetisavailable.As70%ofourtransactions are through online, this initiative will help to reach our customers and farmers. This will also encourage good and profitable production of vegetables and fruits.